Secure E - Medical record system - Law, Jennifer (University Malaysia Sarawak, UNIMAS., 2005)
This project is developed mainly as a requirement of the degree. This project is a under the supervision of En. Johari Abdullah and is being examined Pn. Kartinah Zen. Secure e-Medical Record System, serving the purpose to enhance the medical record management by authorized administrator. This administrator is an authorized UNIMAS staff. The existing medical records management is done manually. Secure e-Medical Record System defines different access level to the records.